Complejo logístico de distribución y transformación de productos de almidón (2018)
Based on a regional analysis in the municipality of Tunja, there is a series of needs at functional, environmental and socioeconomic levels. In this way the project is focused on the environmental part according to the existing needs in the region, proposing large environmental restorations to the bandit lands, that is to say the lands affected by the bad use or extreme use of chemical fertilizers that deteriorate not only the natural air of the region but also polluting the production of this great agricultural region. For this reason, several alternatives are obtained to satisfy each and every one of the environmental needs that are found in this region, by poor technology and education to users, in this case the farmers who produce this type of inadequate foci to achieve land sustainability and crop production.